Unpacking the compactness-emission nexus with the moderating role of environmental governance: Evidence from urban built-up areas in eastern China - Yating Wang; Mengqiao Song; Jie Wang; Li He; Yecui Hu (Land Use Policy, 2026)

Soybean residue incorporation enhances soil CO₂ emissions by increasing nutrient availability and alleviating microbial phosphorus limitation - Xiongde Dong; Yutong Xiao; Mai-He Li; Shijie Han; Yating Deng; Yanyan Yu; Feirong Ren; Junqiang Zheng (Applied Soil Ecology, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Microplastic removal in field-scale and in-situ water treatment systems: A systematic performance review - Asfandyar Shahab; Licheng Peng; Abubakr M. Idris; He Xiao; Tauseef Ahmad; Yating Luo; Michael S. Bank (Process Safety and Environmental Protection, 2026)

Chitosan oligosaccharides reshape Penicillium digitatum infection responses in 'Harumi' fruit by reinforcing defense signaling and phenolic metabolism - Hengquan Wu; Xun Wang; Panpan Gao; Yating Wang; Tuan Wang; Changpin Chun; Yizhong He; Mingfei Zhang (Postharvest Biology and Technology, 2026)

Construction dual-temperature responsive hydrogel of hydroxypropyl methylcellulose and κ-carrageenan via formation of dynamic semi-interpenetrating physical structure - Mengya Sun; Qiongyu Wang; Jiulong An; Qiaolian Xu; He Li; Xinqi Liu; David Julian McClements; Yating Huang; Zhihua Pang (Carbohydrate Polymers, 2026)

Social context modulates the behavioural effects of physical enrichment in yellowfin seabream Acanthopagrus latus - Yijie He; Zonghang Zhang; Yating Zheng; Wuhan Lin; Wentao Lu; Qiaoling Fu; Wenhua Liu (Applied Animal Behaviour Science, 2026)

Building 3D conductive networks within sponge-like porous carbon nanofibers: A CNT-based cathode strategy for superior microbial fuel cells - Wei Huang; Yating He; Wenyi Yan; Longfei Qiao; Yu Tao; Xiangyu Wei; Xiumei Song; Lin Yang; Lichao Tan; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2026)

No clear preferences for the lineal sex: A comparative study on the differences in progression of parity - Baisensen Zhang; Haiying Zhang; Yating Liu; Chang Fu; Qiao-Qiao He (Behavioral Ecology and Sociobiology, 2026)

Key influencing factors and spatiotemporal patterns of annual net ecosystem CO2 exchange in China - Yating Xu; Guangsheng Zhou; Li Zhou; Haitao Wei; Zhihui Tian; Xiaohui He (Journal of Environmental Management, 2026)

LeafLoDs: A Self-Adaptive 3-D leaf modeling with enhancing level of details expression - Zhenyang Hui; Yating He; Shuanggen Jin; Wenbo Chen; Haiqing He; Yao Yevenyo Ziggah (Computers and Electronics in Agriculture, 2026)

Non-uniform salinity combined with localized nitrogen supply improves water use efficiency and fruit visual and storage qualities in tomato - Jinjing Liu; Zhenchang Wang; Yongfeng Huang; Yuexiong Wang; Weixing Wen; Kexin Chen; Yanmin Bi; Yating He; Jiaming You; Yaosheng Wang (Plant and Soil, 2026)

Telomere-to-telomere genome assembly reveals the genomic architecture of disease resistance and yield coordination in elite wheat YM33 - Guofeng Lv; Yating Wang; Heping Zhang; Yuning Shen; Wenjing Hu; Datong Liu; Mengmeng Liu; Wenna Wang; Yuwen Gao; Caixia Lan; Tongde Bie; Hongya Wu; et al. (Molecular Plant, 2026)

Correlation analysis of monosaccharide composition and in vitro antioxidant and hypoglycemic activities of Tremella fuciformis spore polysaccharides - Jianqiu Chen; Xiaoyu He; Shuting Zhou; Yujie Chen; Chunyuan Kong; Yating Deng; Shikai Ruan; Chengzhen Gu; Shujing Sun (Food Chemistry, 2026)

Colloidal properties of protein-stabilized emulsions in the presence of saliva: Impact on oral lubrication and sensory perception - Mengya Sun; Wenyan Tan; Yating Huang; David Julian McClements; Yongbao Wei; He Li; Zhihua Pang; Xinqi Liu (Food Research International, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Sodium alginate-mediated interfacial structuring in soy protein-quercetin composite emulsions: A synergistic strategy for encapsulation and bioavailability enhancement of lipophilic bioactives - Taoran Li; Zifan Zhang; Juanjuan Shao; Xuehui Wu; Heran Xie; Beibei Zhu; Xinyi He; Hongwu Wang; Yating Zhang (Food Chemistry, 2025)

New pterosins from Hypolepis punctata - Liang Shen; Wenhao Mu; Peixin Wang; Maoni Ren; Yating Jia; Xiaoran Min; Jiajia He; Guozheng Huang; Hui Shen; Jianguo Cao (Journal of Natural Medicines, 2025)

Community Distribution of Endophytic Bacteria in Nodules of Vicia villosa in Rocky Desertification Area of Southwest China - Yuanyuan Qi; Jinhuan Cheng; Xinyue Zhang; Li Yao; Yating He; Qiuli Yan; Jinhua Wang (Current Microbiology, 2025)

Spatial and temporal trade-offs between carbon storage and crop production in Chinese terrestrial ecosystems, 1995–2100 - Yating He; Youjia Liang; Chunzhu Shen; Xinguo Bu; Jing Wang (Journal for Nature Conservation, 2025)

On-site tracking of trace Aflatoxin B1 in food waste composting via a portable colorimetric sensing platform with nanozymes - Yating Lu; Fuqing He; Xu Zhu; Jing Tang; Yue Lu; Jiajia Wang; Jiangfang Yu; Li Chen; Xingyang Cheng; Tianhao Liu; Lin Tang (Journal of Hazardous Materials, 2025)

Effective role and mechanism of scrap iron filings in controlling hydrogen sulfide production in septic tanks - Zhiqiang Zhang; Shanshan Song; Wanze He; Xiaowei Ren; Yating Ren; Honglin Yuan; Heliang Pang; Jing Yang; Jinsuo Lu (Journal of Hazardous Materials, 2025)

GhCTEF2 encodes a PLS-type PPR protein required for chloroplast development and plastid RNA editing in cotton - Huan He; Mengxue Cheng; Bowen Bao; Yanan Tian; Yating Zheng; Yuzhu Huo; Zengqiang Zhao; Zongming Xie; Jianing Yu; Peng He (Plant Science, 2025)

Identification of microplastics in human tear fluid and meibum: Implications for dry eye disease pathogenesis - Jingyi Wang; Huanmin Kang; Xixuan Huang; Yating Liu; Yan He; Ying Jie (Journal of Hazardous Materials, 2025)

Sustainable microbial fermentation of plant Proteins: Potential, biological resources, fermentation mechanisms, applications and challenges in food industry - Maosi Fan; Xuelian He; Yating Cao; Kalekristos Yohannes Woldemariam; Min Cai; Zhengkai Wang; Yushan Jiao; Wensheng Tang; Xiaoming Wei; Yingli Liu; Jing Wang (Food Bioscience, 2025)

Solar interfacial evaporation based on bio-aerogel materials: A review - Ying Zhang; Jiehui Li; Yuhang Gao; Pu Feng; Yuan Deng; Jinmei He; Yating Zhang; Mengnan Qu (Desalination, 2025)

Surface whitening prevention strategy of the mural relics from consolidation treatment: An innovative calcium protectant - Lu Wang; Zixuan Wang; Yating Wang; Guang Huang; Yalong Xing; Fuwei Yang; Zhang He; Yan Liu; Yifei Miao; Shaoxuan Niu (Chemical Engineering Journal, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Characteristics and Prediction of Reservoir Water Quality under the Rainfall-Runoff Impact by Long Short-Term Memory Based Encoder-Decoder Model - Xiaodan Sheng; Yulan Tang; Shupeng Yue; Xu Yang; Yating He (Water Resources Management, 2025)

How climate risks relate to Chinese green finance markets in time-frequency domains? A consideration of extreme market conditions - Rongyan Liu; Lingyun He; Ling Chen; Yating Fu (Journal of Cleaner Production, 2025)

Transparent mechanism of salted egg (white) hierarchically and synergistically driven by NaCl, NaOH and thermal treatment: Based on empirical data and molecular simulation - Le Chen; Shiqin Dong; Peng Xu; Zhuosi Yu; Yating He; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

A Global Synthesis of Environmental Enrichment Effect on Fish Stress - Zonghang Zhang; Yijie He; Jiujiang Wang; Yating Zheng; Jiezhang Mo; Xiumei Zhang; Wenhua Liu (Fish and Fisheries, 2025)
The stress‐coping ability (SCA) is one of the core aspects of fish welfare and is of vital importance for fish production in the aquaculture industry and for fish fitness in hatchery release. Environmental enrichment (EE), a method of introducing external stimuli into the husbandry environment, has been recently proposed to improve fish SCA, but the present experimental evidence is mixed, and the reasons for these discrepancies are unclear. Here, we conducted a global meta‐analysis using a data set that consists of 1786 cases from 107 studies across 42 fish species to solve this problem. Overall, we found that enriched fish had significantly higher SCA than control fish, reflected in either basal stress levels or stress responses. Meta‐regression analyses showed that specific subgroups of enrichment type, fish developmental stage, stress category, stress duration, stress place, sample tissue and indicator system showed significant positive EE effects on SCA. Multi‐model inference indicated that the indicator system, fish developmental stage, stress characteristic and enrichment mode are important drivers for the high heterogeneity among effect sizes. These results highlight the importance of introducing EE into the rearing systems, which will not only increase the welfare of aquaculture fish but also improve the ecological adaptability of released fish. The comprehensive knowledge obtained in this analysis will provide insights into fish ontogenetic plasticity and its responses to EE and have important implications for improving the production cycle in fish aquaculture and fisheries conservation.

Are the impacts of uncertainties on clean and conventional energy markets symmetrical? A fresh comparison analysis based on direction, quantile, and time-domain - Ling Chen; Lingyun He; Rongyan Liu; Yating Fu (Environment, Development and Sustainability, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Autophagy accompanying the developmental process of male germline stem cells - Zhuofei Jiang; Liji Chen; Tao Wang; Jie Zhao; Shuxian Liu; Yating He; Liyun Wang; Hongfu Wu (Cell and Tissue Research, 2024)

Maximum diving duration and its influencing factors of diving lizards - Niujin Shi; Yating Liu; Sanqi Tang; Shuyi Luo; Jiasong He; Zhengjun Wu (Behavioral Ecology and Sociobiology, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

Research on the economic agents' green co-evolution of China: Framework, model, and application - Ling Chen; Lingyun He; Rongyan Liu; Yating Fu; Quanhui Yang (Journal of Cleaner Production, 2024)

A stable delivery system for curcumin: Fabrication and characterization of self-assembling acylated kidney bean protein isolate nanogels - Zhihui Yu; Yating Gao; Ziqi Shang; Tengfei Wang; Xuli He; Jian Lei; Fei Tai; Lixin Zhang; Yisheng Chen (Food Chemistry, 2024)

Genome-wide identification and expression analysis of the universal stress protein (USP) gene family in Arabidopsis thaliana, Zea mays, and Oryza sativa - Mingxia Fan; Song Gao; Yating Yang; Shuang Yang; He Wang; Lei Shi (Genetica, 2024)

Undescribed cytotoxic bisabosqual-type meroterpenoids from an endophytic Stachybotryaceae sp. associated with Delphinium yunnanense - Hongtao Li; Changyan Li; Cuiping Miao; Yating Shao; Wenyu Huang; Bo He; Wei Li (Phytochemistry, 2024)

Enhancement of carbon sink in the main marginal sea ice zone by cold season Arctic cyclones - Yujun Liu; Yijun He; Yating Shao (Science of The Total Environment, 2024)

Response of fulvic acid linking to redox characteristics on methane and short-chain fatty acids in anaerobic digestion of chicken manure - Yating Chen; Zebin Tian; Yan Wang; Chuanyan Zhang; Liangzi He; Xinyu Zhao (Journal of Environmental Management, 2024)

Research on the impact of green mergers and acquisitions of heavily polluting enterprises on the quality of environmental information disclosure: empirical evidence from listed companies in China - Suchao He; Yating Wei; Wenping Li (Environment, Development and Sustainability, 2024)
Green mergers and acquisitions are an important means for heavily polluting enterprises to achieve green transformation. Previous studies have yielded inconsistent conclusions regarding the relationship between green mergers and acquisitions and the level of corporate environmental management, possibly due to the omission of considering the quality of corporate environmental information disclosure. Therefore, based on a sample of 908 observations of heavily polluting listed companies on the A-share market of Shanghai and Shenzhen from 2010 to 2019, Utilizing a fixed-effects model, this study empirically examines the relationship between green mergers and acquisitions and the quality of environmental information disclosure and further explores the boundary effects of government environmental regulation and property rights on this relationship. The results show that green mergers and acquisitions of heavily polluting enterprises have a significantly positive impact on the environmental information disclosure quality of acquiring firms, and government environmental regulation positively moderates the relationship between green mergers and acquisitions and environmental information disclosure quality. Through subgroup analysis based on different property rights, it is found that compared to non-state-owned enterprises, state-owned enterprises exhibit a stronger positive relationship between green mergers and acquisitions and the quality of environmental information disclosure. This study has further enriched the relevant literature on green M&A and environmental information disclosure, provided new ideas for heavy polluting enterprises to achieve green transformation, and provided a reference for the government and enterprises to take countermeasures and suggestions.

Spatiotemporal control of DNAzyme activity for fluorescent imaging of telomerase RNA in living cells - Yating He; Kemei Jiang; Bojun Liu; Hong-Min Meng; Zhaohui Li (Analytica Chimica Acta, 2024)

Loss of green landscapes due to urban expansion in China - Yating He; Youjia Liang; Lijun Liu; Zhangcai Yin; Jiejun Huang (Resources, Conservation and Recycling, 2023)

Induced Resistance Mechanism of Bacillus velezensis S3-1 Against Pepper Wilt - Yongjie Fan; Xingjie He; Jiawei Dai; Ning Yang; Qiuyan Jiang; Zhaofeng Xu; Xiaorong Tang; Yating Yu; Ming Xiao (Current Microbiology, 2023)

Study on the formation pathways of characteristic volatiles in preserved egg yolk caused by lipid species during pickling - Zhuosi Yu; Lin Ye; Yating He; Xinhong Lu; Le Chen; Shiqin Dong; Xiaole Xiang (Food Chemistry, 2023)

The underappreciated importance of solar radiation in constraining spring phenology of temperate ecosystems in the Northern and Eastern United States - Yating Gu; Yingyi Zhao; Zhengfei Guo; Lin Meng; Kun Zhang; Jing Wang; Calvin K.F. Lee; Jing Xie; Yantian Wang; Zhengbing Yan; He Zhang; Jin Wu (Remote Sensing of Environment, 2023)

A Genome-Wide Association Study for Susceptibility to Axial Length in Highly Myopic Eyes - Qiang Lu; Yu Du; Ye Zhang; Yuxi Chen; Hao Li; Wenwen He; Yating Tang; Zhennan Zhao; Yinglei Zhang; Jihong Wu; Xiangjia Zhu; Yi Lu (Phenomics, 2023)

Mesophilic Anaerobic Digestion of Arundo donax cv. Lvzhou No. 1 and Pennisetum giganteum for Biogas Production: Structure and Functional Analysis of Microbial Communities - Yuyang Qiu; Yating Lei; Hui Zhao; Xiaoyu He; Bin Liu; Ying Huang (BioEnergy Research, 2023)

Seasonal effects on aboveground biomass estimation in mountainous deciduous forests using ZY-3 stereoscopic imagery - Wenjian Ni; Tianyu Yu; Yong Pang; Zhiyu Zhang; Yating He; Zengyuan Li; Guoqing Sun (Remote Sensing of Environment, 2023)

Remediation of heavy-metal-contaminated soil with two organic acids: Washing efficiency, recovery performance, and benefit analysis - Zilin He; Lulu Long; Han Yuan; Han Pang; Yating Wang; Liang Ye; Min Xu; Chao Chen; Yan Liu; Yinlong Xiao; Changlian Xu; Jun Wu; et al. (Journal of Cleaner Production, 2023)

Assembled denitrifying consortia for efficient nitrate removal under low-COD/N conditions - Meng Jiang; Yating Wu; Penghui He; Shiyin Hu; Qingxi Li; Shouwen Chen (Chemical Engineering Journal, 2023)

Theoretical investigation on the inert pair effect of Ga on both the Ga-Ni-Mo-S nanocluster and the direct desulfurization of 4,6-dimethyldibenzothiophene - Fei Fan; Zhiping Chen; Anning Zhou; Zhiyuan Yang; Yating Zhang; Xinxin He; Jie Kang; Wenwu Zhou (Fuel, 2023)

Oxalic acid enhances bioremediation of Cr(VI) contaminated soil using Penicillium oxalicum SL2 - Bibo Long; Lingling Liao; Fei Jia; Yating Luo; Junyu He; Wenhua Zhang; Jiyan Shi (Chemosphere, 2023)

Inhalation cancer risk estimation of source-specific personal exposure for particulate matter–bound polycyclic aromatic hydrocarbons based on positive matrix factorization - Bin Han; Yan You; Yating Liu; Jia Xu; Jian Zhou; Jiefeng Zhang; Can Niu; Nan Zhang; Fei He; Xiao Ding; Zhipeng Bai (Environmental Science and Pollution Research, 2019)

cDNA cloning of gs, gogat, and gdh from Haematococcus pluvialis and transcription and enzyme level analysis in different nitrogen concentration - Yating Ding; Xiaonan Zang; Jiawei Shi; Lulu Hou; Bangxiang He; Manman Dong; Xiaomei Cong; Xuexue Cao; Zhu Liu; Xinwei Song; Xiaoyun Huang; Xuecheng Zhang (Journal of Applied Phycology, 2019)

Tectonothermal Records in Migmatite-Like Rocks of the Guandi Complex in Zhoukoudian, Beijing: Implications for Late Neoarchean to Proterozoic Tectonics of the North China Craton - Yating Zhong; Chuan He; Neng-Song Chen; Bin Xia; Zhiqiang Zhou; Binghan Chen; Guoqing Wang (Journal of Earth Science, 2018)

Cloning and transcription analysis of the nitrate reductase gene from Haematococcus pluvialis - Lu-lu Hou; Feng Liu; Xiaonan Zang; Xuecheng Zhang; Bangxiang He; Yating Ding; Xinwei Song; Dongfang Xiao; Haitao Wang (Biotechnology Letters, 2017)

Assessing the inhalation cancer risk of particulate matter bound polycyclic aromatic hydrocarbons (PAHs) for the elderly in a retirement community of a mega city in North China - Bin Han; Yating Liu; Yan You; Jia Xu; Jian Zhou; Jiefeng Zhang; Can Niu; Nan Zhang; Fei He; Xiao Ding; Zhipeng Bai (Environmental Science and Pollution Research, 2016)

RNA interference-mediated repression of SmCPS (copalyldiphosphate synthase) expression in hairy roots of Salvia miltiorrhiza causes a decrease of tanshinones and sheds light on the functional role of SmCPS - Qiqing Cheng; Ping Su; Yating Hu; Yunfei He; Wei Gao; Luqi Huang (Biotechnology Letters, 2014)

Effects of a conversion from grassland to cropland on the different soil organic carbon fractions in Inner Mongolia, China - Yuchun Qi; Yunshe Dong; Qin Peng; Shengsheng Xiao; Yating He; Xinchao Liu; Liangjie Sun; Junqiang Jia; Zhijie Yang (Journal of Geographical Sciences, 2012)

Soil nitrous oxide emissions from a typical semiarid temperate steppe in inner Mongolia: effects of mineral nitrogen fertilizer levels and forms - Qin Peng; Yuchun Qi; Yunshe Dong; Shengsheng Xiao; Yating He (Plant and Soil, 2011)

Spatial-temporal variation in soil respiration and its controlling factors in three steppes of Stipa L. in Inner Mongolia, China - YuChun Qi; YunShe Dong; LiXin Liu; XingRen Liu; Qin Peng; ShengSheng Xiao; YaTing He (Science China Earth Sciences, 2010)